Decarbonization in Shipping Industry: A Review of Research, Technology Development, and Innovation Proposals - George Mallouppas; Elias Ar. Yfantis (Journal of Marine Science and Engineering, 2021)
This review paper examines the possible pathways and possible technologies available that will help the shipping sector achieve the International Maritime Organization’s (IMO) deep decarbonization targets by 2050. There has been increased interest from important stakeholders regarding deep decarbonization, evidenced by market surveys conducted by Shell and Deloitte. However, deep decarbonization will require financial incentives and policies at an international and regional level given the maritime sector’s ~3% contribution to green house gas (GHG) emissions. The review paper, based on research articles and grey literature, discusses technoeconomic problems and/or benefits for technologies that will help the shipping sector achieve the IMO’s targets. The review presents a discussion on the recent literature regarding alternative fuels (nuclear, hydrogen, ammonia, methanol), renewable energy sources (biofuels, wind, solar), the maturity of technologies (fuel cells, internal combustion engines) as well as technical and operational strategies to reduce fuel consumption for new and existing ships (slow steaming, cleaning and coating, waste heat recovery, hull and propeller design). The IMO’s 2050 targets will be achieved via radical technology shift together with the aid of social pressure, financial incentives, regulatory and legislative reforms at the local, regional and international level.